Rational manipulation of composition and construction toward Zn/Co bimetal hybrids for electromagnetic wave absorption. (20th January 2023) - Ren, Xiuyun; Song, Yihe; Gao, Zhenguo; Wu, Yalan; Jia, Zirui; Wu, Guanglei
Highlights: Zn@Co and Co@ Zn/Co bimetal hybrids were fabricated by bi-orientation etching strategy. The components and constructions are regarded as major factors determining electromagnetic properties. The RLmin and f E of Zn@Co-C-2h reached −34.99 dB and 5.52 GHz (2.00 mm), respectively. Abstract: Rational manipulation of multi-metal hybrids with controllable compositions and constructions is evolving as an efficacious strategy for tunable electromagnetic (EM) characteristics and EM wave (EMW) absorption. Herein, a novel bi-orientation etching approach is proposed to regulate the chemical compositions and hybridization construction of Zn/Co hybrids, thence meeting the synergistic interaction among diverse compositions for ultra-high EMW absorption. Attributing to the stepwise heterometallic modification by Zn in Co-ZIFs (Zn@Co-ZIF) and Co in Zn-ZIFs (Co@Zn-ZIF), corresponding pyrolysis products with variable Zn/Co atomic concentration and hybridization states (Zn@Co-C, Co@Zn-C) can be obtained. The Co species was confirmed to have a positive impact on both the dielectric and magnetic response, while an appropriate amount of Zn hybridization in Co substance further enhanced the synergistic effect between multiple loss mechanisms, promoting the minimum reflection loss and effective absorption bandwidth of Zn@Co-C reached -34.99 dB and 5.52 GHz (2.00 mm), respectively. Finally, this work reveals the composition and construction dependency of bimetal hybrids on EMW absorption, which can be a strong reference for developing EMAs with diverse hybridization structures.